Combining realist reviews with realist evaluations - Wong, G; Howe, J; MacPhee, M; Maidment, I (Routledge, 2024)
Increasingly, researchers are conducting projects that combine realist reviews with realist evaluation. This combination can have benefits, but is likely to increase the cost, duration and complexity of the project. This chapter provides advice on four areas that need to be considered when planning to run a combined project: staffing, sequencing, data collection and analysis. With staffing there is no ‘perfect’ number of researchers to have on the project; instead thought should be given to the pros and cons of any staffing arrangement. Having administrative support can help. Time should be spent on building a well-functioning project team. When sequencing, realist reviews are commonly conducted first, but it may be acceptable to start primary data collection when a ‘good enough’ programme theory has been developed from the review. When gathering data, having a team with the correct skill mix matters, as does a realistic timeframe that provides space for discussion, analysis and reflection. Data collection methods should adhere to any existing quality standards. Finally, it is important to develop and agree on a coherent data analysis plan and processes; regular data analysis can help, as can respectful and consistent input from stakeholders.